Provision of Universal Design Educational Material Following a Homeowner's Insurance Claim. Issue 3 (2nd July 2016) - Beck, Patrick; Enguidanos, Susan; Rahman, Anna; Nabors, Emily; Tracton-Bishop, Beth; Olshevski, Jodi; Pynoos, Jon
ABSTRACT: Although most older adults prefer to age in place, their homes often lack supporting features. Universal design (UD) modifications help promote independence and reduce the risk of accidents. This study investigated whether educating homeowners about UD following a home disaster influenced the repairs they made. Home insurance policyholders who submitted claims for damage to bathrooms or kitchens received an educational brochure introducing UD features. Homeowners completed follow-up surveys with questions about home modifications made, respondents' demographic characteristics, and householders' ability to perform activities of daily living (ADLs). Descriptive and bivariate analyses were conducted. Thirty-three of 37 respondents (89.2%) had implemented UD modifications, making an average of 9.1 UD modifications. Most respondents rated the brochure information positively and respondents' self-rated knowledge of UD improved after reading the brochure. The number of modifications made was positively associated with a householder having limitations in meal preparation, but not other ADL or functional limitations. Homeowners in the midst of repairing their home following an insurance claim and who received educational information about UD options implemented UD modifications, which could increase UD-modified housing stock and enhance the capacity for future generations to age in place.